Aquatic plants of Pennsylvania : a complete reference guide - Rhoads, Ann Fowler (University of Pennsylvania Press, 2011)
From the Delaware River to the shores of Lake Erie, Pennsylvania's diverse watery habitats are home to more than 200 species of aquatic plants. In Aquatic Plants of Pennsylvania: A Complete Reference Guide, botanists Timothy A. Block and Ann Fowler Rhoads have assembled the first identification guide specific to the Keystone State yet useful throughout the Mid Atlantic region. Organized and written in a way that will make information easily accessible to specialists and nonspecialists alike, the book highlights the diversity and vital ecological importance of this group of plants, providing photographs, illustrations, descriptions, and identification keys for all emergent, floating-leaved, and submergent aquatic plants found in the Commonwealth.An introductory chapter on aquatic plant ecology covers topics such as evolution, form, and reproduction of aquatic plants, vegetation zones, types of aquatic ecosystems, and rare and endangered species. Information on invasive plants, such as Eurasian water-milfoil and curly pondweed, that threaten Pennsylvania's aquatic ecosystems will be especially useful to watershed organizations, citizen monitoring projects, lake managers, and natural resource agency personnel. An illustrated identification key guides the reader through a series of steps to properly identify a specimen based on its characteristics. Each of the more than 200 listings provides a plant's taxonomy, detailed description, distribution map, and expert botanical illustrations. Many also include color photographs of the plants in their natural habitats.